2022
DOI: 10.1002/adfm.202206014
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Robust Superamphiphobic Coatings Enabled by Self‐Similar Structure, Protective Micro‐Skeleton, and Adhesive for Practical Anti‐Icing of High‐Voltage Transmission Tower

Abstract: Superamphiphobic coatings have wide application prospects in various fields, but suffer from low mechanical robustness. Although some strategies have been reported to solve the issue, it is still challenging for large‐scale preparation of robust superamphiphobic coatings via facile approaches. Here, a universal preparation method of mechanically robust superamphiphobic coatings by spraying a suspension containing silica nanoparticles decorated with perfluorodecyl polysiloxane and adhesive microparticles on var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 41 publications
3
66
0
Order By: Relevance
“…1−3 Because of their special wettability, these materials are promising for selfcleaning, 4,5 oil/water separation, 6,7 corrosion resistance, 5,8,9 biological techniques, 10−12 and anti-icing. 13,14 Among various functional superhydrophobic coatings, luminescent superhydrophobic coatings have generated particular interest and developed rapidly. They have widespread applications in sunlight conversion of agriculture, 15−17 anticounterfeiting technologies, 18,19 bioimaging 20,21 and optoelectronic devi-ces.…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Because of their special wettability, these materials are promising for selfcleaning, 4,5 oil/water separation, 6,7 corrosion resistance, 5,8,9 biological techniques, 10−12 and anti-icing. 13,14 Among various functional superhydrophobic coatings, luminescent superhydrophobic coatings have generated particular interest and developed rapidly. They have widespread applications in sunlight conversion of agriculture, 15−17 anticounterfeiting technologies, 18,19 bioimaging 20,21 and optoelectronic devi-ces.…”
Section: Introductionmentioning
confidence: 99%
“…It is meaningful and necessary that the icing time and ice adhesion force on the coatings should be provided before studying the photothermal deicing performance. In order to clarify the deicing performances, the FM coating was studied according to the literature. , A camera was used to film the whole process of water droplets from cooling to solidification, as shown in Figure S23. Before the experiment, because the CA of the DTHL 2 surface is different from that of the FM superhydrophobic surface, it is observed that the water droplets present different shapes on different surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Superhydrophobic surfaces have unique wetting behaviors, including a high water contact angle (CA) of >150° and a low sliding angle (SA) of <10°. In recent decades, superhydrophobic coatings have attracted increasing attention in diverse fields including self-cleaning, anti-icing, , corrosion resistance, , antibiofouling, , drag reduction, , and oil/water separation. , In order to prepare superhydrophobic coatings, the construction of micro-/nanostructures and the reduction of surface energy are essential. , Perfluorinated compounds with long carbon chains (such as perfluorooctanoic acid) are widely used for preparing superhydrophobic coatings due to their very low surface energy (∼10 mJ m –2 ), good weather resistance, heat resistance, and chemical stability . For example, Boban et al prepared superhydrophobic coatings with fluorinated polyurethane and fluorodecyl polyhedral oligomer polysiloxane .…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic surfaces have unique wetting behaviors, including a high water contact angle (CA) of >150°and a low sliding angle (SA) of <10°. In recent decades, superhydrophobic coatings have attracted increasing attention in diverse fields including self-cleaning, 1−3 anti-icing, 4,5 corrosion resistance, 6,7 antibiofouling, 8,9 drag reduction, 10,11 and oil/water separation. 12,13 In order to prepare superhydrophobic coatings, the construction of micro-/nanostructures and the reduction of surface energy are essential.…”
Section: ■ Introductionmentioning
confidence: 99%